The combined effect of Sango sprout juice and caloric restriction on metabolic disorders and gut microbiota composition in an obesity model. (17th February 2018) - Vivarelli, Fabio; Canistro, Donatella; Babot Marquillas, Clara; Cirillo, Silvia; De Nicola, Gina R.; Iori, Renato; Biagi, Giacomo; Pinna, Carlo; Gentilini, Fabio; Pozzo, Luisa; Longo, Vincenzo; Paolini, Moreno
Abstract: The main purpose of this study was to compare the benefits of SSJ supplementation in obese rats with those achieved only by switching the alimentary regimen from high-fat (HFD) to the regular one (RD) in liver, ileum and prostate. Furthermore, changings in caecal chime microbiota were investigated. SSJ was administered to rats in combination with a RD (HFD-RD + SSJ). The switch from HFD to RD led to a weight loss of almost 9.8 g, and the total cholesterol was found to be significantly lower. In the HFD-RD + SSJ group, all values were improved compared with the HFD control, and the weight decrement was higher (−23.29 g) with respect to HFD-RD. HFD led to a widespread increment of oxidative stress (OS) markers in liver, ileum and prostate. SSJ has shown to improve the results achieved by the suspension of HFD and it has proven effective wherever the only switch in diet regimen failed.